2014
DOI: 10.1016/j.jgr.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ginsenoside Re on acute gastric mucosal lesion induced by compound 48/80

Abstract: The protective effect of ginsenoside Re, isolated from ginseng berry, against acute gastric mucosal lesions was examined in rats with a single intraperitoneal injection of compound 48/80 (C48/80). Ginsenoside Re (20 mg/kg or 100 mg/kg) was orally administered 0.5 h prior to C48/80 treatment. Ginsenoside Re dose-dependently prevented gastric mucosal lesion development 3 h after C48/80 treatment. Increases in the activities of myeloperoxidase (MPO; an index of neutrophil infiltration) and xanthine oxidase (XO) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…and ginsenosides in Panax quinquefolius L. and Panax ginseng C.A. Meyer [3]. Their pharmacological activities, including anti-inflammatory [4], hypoglycemic [5], immunological adjuvant [6], and anti-endotoxin [7] properties, have been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…and ginsenosides in Panax quinquefolius L. and Panax ginseng C.A. Meyer [3]. Their pharmacological activities, including anti-inflammatory [4], hypoglycemic [5], immunological adjuvant [6], and anti-endotoxin [7] properties, have been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the ginseng berry also exhibits anti-cancer activity in in vitro [2, [73][74][75][76][77] and in vivo [2, 78,79], as well as the ability to attenuate chemotherapy-induced side effects [80,81]; these effects result from the promotion of dendrite cell maturation. Interestingly, the ginseng berry induced a higher degree of co-stimulatory molecule up regulation than the root extract at the same concentrations [82].…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…Ginsenosides (GS) is a group of active compounds present in the ginseng (Oh et al, 2014) and was reported to protect the ginseng root from microbial and fungal infections (Wu et al, 2014). Numerous studies showed that GS have a number of biological effects, including antioxidant and antihyperlipidaemic efficacies in streptozotocin-induced diabetic (Cho et al, 2006); protective effect on acute mucosal lesion (Lee et al, 2014); anti-amnestic, antiageing and antistress effects (Cheng et al, 2005); antiallergic activity (Bae et al, 2002); lowering cholesterol and protecting body from lethal infection of haemagglutinating virus (Yoo et al, 2013); protective benefits against neurotoxicity (Li et al, 2011); and metastasis of cancer cells (Yoon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%